Pengaruh Perceived Ease of Use, Brand Image, dan Harga terhadap Keputusan Pembelian (Studi pada Pengguna Transportasi Online Maxim di Kota Medan) - Ray, Laila Afrina; Siregar, Onan Marakali (Prodi Manajemen, Fakultas Ekonomi, Universitas Pamulang, 2024)
Purchasing decisions are one of the important factors in marketing a service. The lack of consumer purchase interest in Maxim online transportation services makes Maxim less recognized by the people of Medan. Factors that can influence purchasing decisions such as perceived ease of use, brand image, and price. The form of research used is quantitative with an associative approach. The population in this study is the community of Maxim online transportation service users in Medan City, with a sample of 96 respondents, with a sampling technique using purposive sampling. Primary data were obtained through direct distribution of questionnaires and secondary data were obtained through literature studies. The results of this study showed that Perceived Ease of Use did not significantly affect the Purchase Decision, with a sig value of 0.203 > 0.05. Brand Image has a significant positive effect on Purchase Decisions with a significance of 0.000 < 0.05. Price also has a significant positive effect on Purchasing Decisions with significance levels of 0.005 < 0.05. In simultaneous testing, the variables Perceived Ease of Use, Brand Image, and Price had a simultaneous effect with an influence rate of 46.8%, while the remaining 53.2% was influenced by factors outside this research model.